Vigilancia ambiental de efluentes generados por la actividad acuícola continental, distrito de Moyobamba - Mesía Bartra, Jorge David (2015)
The progressive increase in aquaculture activity in the Moyobamba district is reflected in the increase in the consumption of commercial food for fish - Balanced extruzado,..mainly the smaller-scale 100% throug·hoÜt its productive process, this contributes to vary the conditions of the water quality of the effluent in view that not all the provided food is consumed. Through this research work was managed to determine the degree of concentration of water quality parameters essential for the development of acuicula activity as are: Total suspended solids, Biochemical Oxygen Demand, dissolved oxygen, pH and temperature; the total number of farms were monitored 03 owned by Messrs. Paul Angulo Vargas located in the sulfurous baths, Cristir Águila Cruz located in the Port Sector Motilones and Harold Donald Henry located in the Perla lndañe Sector, for a time of 03 months, that were selected by the start date of the productive process, use of balanced food in a 100 per cent in the whole process, with equal product planting density and species. The monitoring consisted of placing two stations for each fish farm evaluated, one at the entrance of water to the fish-breeding farm and another in the discharge pipe of the effluent from the pond which is in production; the frequency of monitoring were intervals of thirty days for a time period of three consecutive months. As a result of the assessment the effluents generated from the farm owned by Mr. Cristir Aguila Cruz - Monitoring Station No. 02 exceeds the ECAs established for total suspended solids in 50.7 ppm. In regard to the Biochemical Oxygen Demand the effluents of the 03 fish farms evaluated exceed the range of the ECAs established by Decree No 002-2008-M1 NAM - Water Quality Standards for jungle rivers, with 6.1 mg/1, 6.2 mg/1 and 6.2 mg/1 respectively. In regard to the equivalent averages in comparison with the quality of the water of revenue to the fish farms, there is an increase of total solids in suspension of 341.9 ppm that represents the 812.1%; the Biochemical Oxygen Demand 0805 is increased by 5.7 mg/1 equivalent to 203.6%; Dissolved Oxygen decreases in